2019
DOI: 10.1021/acsami.9b02485
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-Crystalline Hydroxyapatite/Polymer Nanorod Hybrids: Potential Bioplatform for Photodynamic Therapy and Cellular Scaffolds

Abstract: Recently, we found that self-organization of hydroxyapatite (HAp) with poly(acrylic acid) (PAA) leads to the formation of liquid-crystalline (LC) nanorod hybrids that form aligned films and show stimuli-responsive properties. Here, we demonstrate that these biocompatible HAp/PAA hybrid nanorods represent a platform technology as drug nanocarriers for photodynamic cancer therapy and as bioscaffolds for the control of cellular alignment and growth. To use hybrid nanorods as a drug nanocarrier, we introduced meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 42 publications
1
46
0
Order By: Relevance
“…Simultaneously, they have also been studied for drug delivery due to their ease of functionalization (Perez-Juste et al, 2005;Smith et al, 2009). Calcium phosphate nanorods, mainly hydroxyapatite, have been used both as nanocarriers and for bone tissue regeneration in composite scaffolds (Rubin et al, 2003;Nga et al, 2014;Dave et al, 2019;Li et al, 2019;Nakayama et al, 2019).…”
Section: Defining Nanostructuresmentioning
confidence: 99%
“…Simultaneously, they have also been studied for drug delivery due to their ease of functionalization (Perez-Juste et al, 2005;Smith et al, 2009). Calcium phosphate nanorods, mainly hydroxyapatite, have been used both as nanocarriers and for bone tissue regeneration in composite scaffolds (Rubin et al, 2003;Nga et al, 2014;Dave et al, 2019;Li et al, 2019;Nakayama et al, 2019).…”
Section: Defining Nanostructuresmentioning
confidence: 99%
“…107LC nanorod materials of HAp were also developed. (121)(122)(123)(124) Due to biocompatibility and osteoconductivity, HAp has attracted much attention as biomaterials including artificial bones, and dental implants Control of morphologies and orientation is important for HAp-based materials. Amorphous calcium phosphate stabilized by PAA was used for precursors to develop HAp colloidal liquid crystals.…”
Section: Lc Nanorod and Nanodisk Hybrids Inspired By Biomineralsmentioning
confidence: 99%
“…Oriented HAp thin solid films with unidirectional alignment and radial alignment were obtained by mechanical shearing and spincoating of the LC colloids of HAp nanorods, respectively. (121,123) It was shown that HAp nanorod hybrids was used as drug nanocarriers for photodynamic cancer therapy and can also act as bioscaffolds for cellular alignment and growth. (123)…”
Section: Lc Nanorod and Nanodisk Hybrids Inspired By Biomineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 For example, hydroxyapatite/polymer hybrid nanorods exhibit colloidal liquid-crystalline (LC) states that are responsive to magnetic elds and biocompatible properties. [15][16][17] Development of sustainable materials is important to address global environmental issues. Biominerals are structurally controlled biological hard tissues such as nacre from seashells and egg shells, which are good models for sustainable materials.…”
Section: Introductionmentioning
confidence: 99%